PELATIHAN BATIK JUMPUTAN DI RUMAH YATIM PAMULANG TANGERANG - Hartatik; Ochita Ratna Sari; Putri Rahmawati; Ana Triana Imansari; Fanny Fanny; Dwi Putri Badriyahni; Lesi Andraini; Adinda Nurul Fauziah; Herlyn Istriana Sari; Rindiyanti Rahayu (BHAKTI: JURNAL PENGABDIAN DAN PEMBERDAYAAN MASYARAKAT, 2026)
The jumputan batik training activity for children at the Pamulang Orphanage is a community service program that aims to improve the creative skills and economic independence of orphanage children. This training was initiated by PPG Pre-service students of the Open University in the framework of the Leadership Project task as an implementation of leadership values, social empathy, and educational innovation based on local culture. Jumputan batik was chosen because the technique is simple, environmentally friendly, and has high economic value. The implementation method consists of initial observation, licensing, preparation of activity plans, direct training, mentoring, and evaluation of the work. The results of the activity showed a significant increase in the aspects of creativity, confidence, and interest in children's hand skills activities. The main obstacles in the form of time and material limitations are overcome with adaptive activity management. This training provides dual benefits: for orphanage children as a form of culture-based empowerment, and for students as a vehicle for leadership development and social responsibility.